Hubungan Antara Dukungan Sosial dengan Kesehatan Mental di Indonesia: Kajian Meta-Analisis (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Social support is an essential factor that affects mental health. In the last decade, many studies have been conducted in Indonesia to examine the relationship between social support and mental health. This study aims to investigate the effect size of the relationship between social support and mental health in a study conducted in Indonesia. The meta-analysis research method is used to analyze research conducted from 2012 to 2022. Researchers search through Publish or Perish, Google Scholar, SINTA, Garuda Portal, and Moraref. The keywords used to assist in the search for past research were mental health and social support. Thirty-two studies are included in this meta-analysis study. The data collected in this study are correlation test data and the number of research subjects. Researchers used the JASP application to analyze the random effects model. The results showed that the mean effect of the 32 studies was -0.566, indicating the effect of high social support on mental health. Studies have no publication bias and have heterogeneous effect sizes. Due to the relatively high correlation effect between social support and mental health, it is necessary to predispose to higher social support to prevent mental health problems.